2017
DOI: 10.3389/fpsyg.2017.00717
|View full text |Cite|
|
Sign up to set email alerts
|

“I Want It All, and I Want It Now”: Lifetime Prevalence and Reasons for Using and Abstaining from Controlled Performance and Appearance Enhancing Substances (PAES) among Young Exercisers and Amateur Athletes in Five European Countries

Abstract: Doping use in recreational sports is an emerging issue that has received limited attention so far in the psychological literature. The present study assessed the lifetime prevalence of controlled performance and appearance enhancing substances (PAES), and used behavioral reasoning theory to identify the reasons for using and for avoiding using controlled PAES in young exercisers across five European countries, in the context of the “SAFE YOU” Project. Participants were 800 young amateur athletes and exercisers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
(58 reference statements)
0
32
0
2
Order By: Relevance
“…tend to characterize both competitive and amateur or fitness sport settings (e.g. Lazuras et al, 2017;Sandvik et al, 2018) and to partly depend on users' intention to enhance their performance or physical appearance (i.e. PAES -Performance and Appearance Enhancement Substances).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…tend to characterize both competitive and amateur or fitness sport settings (e.g. Lazuras et al, 2017;Sandvik et al, 2018) and to partly depend on users' intention to enhance their performance or physical appearance (i.e. PAES -Performance and Appearance Enhancement Substances).…”
Section: Discussionmentioning
confidence: 99%
“…The use of Performance and Appearance Enhancing Substances (PAES) that are clearly subject to legal sanctions and often labeled "controlled" 1 has steadily increased among young athletes and exercisers in recent times . A more recent European study of a large sample of young amateur athletes and exercisers has shown that nearly one out of five participants has had experience with controlled PAES in the past (Lazuras et al, 2017).…”
Section: Introduction the Use Of Substances Guided By Performance Andmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many cases, APED use is not a real concern in bodybuilding; the prevalence of APED use among competitive bodybuilders is high, and doping is not perceived as a real moral issue. APEDs are no longer confined to competitive bodybuilders (Griffiths et al, 2017) as they were in the 1960s (Lazuras et al, 2017). Even the meanings associated with APEDs have changed over time.…”
Section: Apeds and Bodybuildingmentioning
confidence: 99%
“…Anabolic androgenic steroids are also often illegally sourced from pharmacies or synthesized in clandestine laboratories. 6 The amateur athletes who most often use anabolic steroids are runners, followed by bodybuilders, cyclists, and weightlifters. The use commonly begins around age 20, and a typical user has at least 1 year of experience training.…”
mentioning
confidence: 99%